The ability of King’s clinical staging and Milano-Torino (MiToS) functional staging in the prediction of amyotrophic lateral sclerosis (ALS) progression: A meta-analysis study - Dr. Mohammed A Maeshi , Dr. Fahad A Majrabi , Dr. Ahlam M Muharraq , Dr. Walaa S Areeshi , Abdulrahman H Alotibi , Dr. GHAIDA Y Alsuhaym , Dr. Torki H Anab , Dr. Abdulsalam S Arishi , Dr. Mohammed A Hakami , Dr. Yahya M Abutalib , Dr. Ramzi A Arishi , DR. Ahmad H Motanbak , Dr. Ismail M Somily , Dr. Khalid M kulaybi , Dr. Abdulaziz A Al Bashir (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by functional connectivity alterations in both motor and extra-motor brain regions. Assessing clinical progression in amyotrophic lateral sclerosis (ALS) remains a challenge. Our objective was to assess the effectiveness, utility, precision, and validity of the King’s staging system and the Milano-Torino Staging (MiToS) system by comparing them in terms of charting disease progression within a clinical setting.